ENHANCING EMPLOYEE PERFORMANCE: THE TRANSFORMATIVE POWER OF GREEN HUMAN RESOURCE MANAGEMENT - Dr. Aajaz Ahmad Hajam,; Alphonsa S John (Universitas Efarina, 2023)
The study aimed to investigate the impact of Green Human Resource Management on the operational effectiveness of private sector firms. A total of twenty studies were included as a sample in this inquiry. The findings of this study indicate that the implementation of Green Human Resource Management has a beneficial impact on the overall performance of a business. Enhancing organizational performance is a crucial determinant of a company's sustainability in the market. The present study's findings indicate that implementing green human resource management methods results in enhanced employee and organizational performance.